Instrumental test of patch antennas manufactured for C-Band applications - Flores Pérez, Daniel Alejandro (2024)
In free space, the calculated wavelength of a 5,2 GHz signal is 57,7 mm, this gives us an idea of ​​the volume required to be occupied by a patch type antenna intended for C-band applications and some of the limitations of relying on a traditional manufacturing process. Considering the interest of competing in the current technological market, it is important to obtain experimental results of the performance of the product that can be obtained with the suggested minimum of resources. Patch antenna prototypes require experimental verifications regardless of the manufacturing process that was carried out, so this work presents a clear methodology that includes calculations, design parameters such as characteristic impedance, acid-based manufacturing, experimental setup with a signal generator and a spectrum analyzer, tests with their respective measurements considering quantitative and qualitative approaches, compatibility with commercial C-band equipment and evaluation of results, providing an experimental comparison of different prototypes of designs based on simple patch antennas and array antennas.